Metrical analysis of disc-condyle relation with different splint treatment positions in patients with TMJ disc displacement (Journal of Applied Oral Science, 2017)
Objective: To evaluate the effect of bite positions characterizing different splint treatments (anterior repositioning and stabilization splints) on the disc-condyle relation in patients with TMJ disc displacement with reduction (DDwR), using magnetic resonance imaging (MRI). Material and Methods: 37 patients, with a mean age of 18.8±4.3 years (7 male and 30 females) and diagnosed with DDwR based on the RDC/TMD, were recruited. MRI metrical analysis of the spatial changes of the disc/condyle, as well as their relationships, was done in three positions: maximum intercuspation (Position 1), anterior repositioning splint position (Position 2), and stabilization splint position (Position 3). Disc/condyle coordinate measurements and disc condyle angles were determined and compared. Results: In Position 1, the average disc-condyle angle was 53.4° in the 60 joints with DDwR, while it was −13.3° with Position 2 and 30.1° with Position 3. The frequency of successful "disc recapture" with Position 2 was significantly higher (58/60, 96.7%) than Position 3 (20/60, 33.3%). In Positions 2 and 3, the condyle moved forward and downward while the disc moved backward. The movements were, however, more remarkable with Position 2. Conclusions: Anterior repositioning of the mandible improves the spatial relationship between the disc and condyle in patients with DDwR. In addition to anterior and inferior movement of the condyle, transitory posterior movement of the disc also occurred.